The 2017 Catalan Independence Referendum: A Symposium. Issue 1 (February 2018) - Cetrà, Daniel; Casanas-Adam, Elisenda; Tàrrega, Mariola
Abstract : This article summarises contributions to an ASEN-Edinburgh (Association for the Study of Ethnicity and Nationalism, Edinburgh Branch) symposium held the day after the 2017 Catalan referendum on independence.Daniel Cetrà describes a referendum disputed between legal and democratic legitimacy and grounded on competing visions of nationhood.Elisenda Casanas-Adam argues that there are alternative interpretations of the Spanish constitution which could accommodate Catalan request and highlights the questionable legality of the Spanish authorities' forceful response.Mariola Tàrrega argues that the Catalan referendum reveals a worrying context where news media become political advocates of opposing worldviews and politicians attribute to news media an overstated capacity to shape nation-building projects.